Influence of protein supplementation during late pregnancy and lactation on the resistance of Santa Ines and Ile de France ewes to Haemonchus contortus - Rocha, R. A. [UNESP]; Bricarello, P. A. [UNESP]; Silva, M. B. [UNESP]; Houdijk, J. G. M.; Almeida, F. A. [UNESP]; Cardia, D. F. F. [UNESP]; Amarante, Alessandro Francisco Talamini do [UNESP] (Elsevier B.V., 2011)
This experiment aimed to evaluate the effect of periparturient metabolizable protein (MP) nutrition on resistance to Haemonchus contortus in single rearing Ile de France and Santa Ines ewes. The restriction-fed iso-energetic diet was calculated to provide either 0.8 (low MP diet) or 1.3 (high MP diet) times MP, from three weeks before parturition until eight weeks into lactation. The ewes were experimentally infected with 1000 H. contortus infective larvae (13) three times a week (Mondays. Wednesdays and Fridays), starting five weeks before the predicted date for parturition until a total of 15,000 L3 had been administered. While both breeds showed elevated fecal egg counts (FEC), these values were significantly lower for Santa Ines ewes than Ile de France ewes, but were independent of level of MP feeding. The latter also did not affect lamb weight gain and ewe body weight variation in each breed. Packed cell volume and total plasma protein for Santa Ines in all periods were significantly higher than those for Ile de France ewes (P < 0.01) but were not affected by nutrition. In contrast, levels of serum IgG and IgA antibodies against somatic H. contortus infective larvae and adult antigens were similar between breeds but higher in animals that received high MP diets (P < 0.05). The reduced body score of ewes at the beginning of the experiment probably influenced their high susceptibility to incoming larvae. Since, unexpectedly, MP scarcity was not achieved in this experiment, our data support the view that Santa Ines ewes are more resistant to H. contortus than Ile de France ewes. (C) 2011 Published by Elsevier B.V.
Keywords: Periparturient; Nutrition; Breed; Resistance; Nematode; Control